2018
DOI: 10.1038/s41386-018-0090-0
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate meta-analyses of mitochondrial complex I and IV in major depressive disorder, bipolar disorder, schizophrenia, Alzheimer disease, and Parkinson disease

Abstract: Complex I (NADH dehydrogenase, NDU) and complex IV (cytochrome-c-oxidase, COX) of the mitochondrial electron transport chain have been implicated in the pathophysiology of major psychiatric disorders, such as major depressive disorder (MDD), bipolar disorder (BD), and schizophrenia (SZ), as well as in neurodegenerative disorders, such as Alzheimer disease (AD) and Parkinson disease (PD). We conducted meta-analyses comparing complex I and IV in each disorder MDD, BD, SZ, AD, and PD, as well as in normal aging. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
152
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(162 citation statements)
references
References 183 publications
8
152
0
2
Order By: Relevance
“…Several post-mortem studies have found both downregulation and upregulation of mitochondria-related genes; particularly those encoding complexes of the ETC ( 55 59 ). Moreover, decreased complex I activity has been reported in the prefrontal cortex of BD patients ( 55 ).…”
Section: Mitochondrial Bioenergeticsmentioning
confidence: 99%
“…Several post-mortem studies have found both downregulation and upregulation of mitochondria-related genes; particularly those encoding complexes of the ETC ( 55 59 ). Moreover, decreased complex I activity has been reported in the prefrontal cortex of BD patients ( 55 ).…”
Section: Mitochondrial Bioenergeticsmentioning
confidence: 99%
“…The proteomics analyses revealed alterations in the expression levels of five subunits of complex I in adult female hippocampus following ELS (Table 2); alterations in complex I expression/activity have been associated with the pathophysiology of several brainbased disorders (Gu et al, 2013;Holper et al, 2018) and observed in animal models following adult metabolic or chronic stress (Emmerzaal et al, 2020;Toniazzo et al, 2019). Based on the iTRAQ discoveries, we next explored whether the protein adaptations to ELS reflected altered function, using an enzyme activity assay in mitochondria isolated from the hippocampus in juveniles and adults.…”
Section: Age-selective Adaptations In Hippocampal Mitochondrial Functmentioning
confidence: 99%
“…Furthermore, complex I subunit protein levels were found to be decreased in different areas of Alzheimer's disease and Down syndrome brain (Kim et al, ), but biochemical studies of enzymatic activity corroborating these findings are lacking in Alzheimer's disease. A meta‐analysis of complex I and complex IV findings found that only complex IV was consistently reported to be decreased in Alzheimer's disease (Holper et al, ). This analysis also showed that decreases of both complexes I and IV were consistently found in studies of human brain ageing (Holper et al, ).…”
Section: Mitochondrial Bioenergetics In Alzheimer's Diseasementioning
confidence: 99%
“…A meta‐analysis of complex I and complex IV findings found that only complex IV was consistently reported to be decreased in Alzheimer's disease (Holper et al, ). This analysis also showed that decreases of both complexes I and IV were consistently found in studies of human brain ageing (Holper et al, ). It is now well established that ageing is associated with lower OXPHOS capacity in human muscle (Trounce et al, ) and, in human, non‐human primate and rodent brain (Bowling et al, ; Ferrandiz et al, ; Ojaimi et al, ).…”
Section: Mitochondrial Bioenergetics In Alzheimer's Diseasementioning
confidence: 99%